Potential Cosmeceuticals from Marine Constituents - Vigneshwaran L.V; Ann Mary Shaju (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Cosmetic pharmaceuticals, or cosmetic goods with drug-like qualities, are the most recent innovation in the pharmaceutical industry. Klingman coined the term